An investigation into cognitive metaphors of “homeland” in trinh cong son’s versus bob dyland’s songs. - Nguyễn,Thị Việt; Đinh Thị MInh Hiền (ĐHĐN : ĐHĐN., 2015)
Adopting Lakoff and Johnson’s famous Conceptual Metaphor Theory, the study looked into an investigation into the Cognitive metaphors of “Homeland” in Trinh Cong Son’s and Bob Dylan’s songs. The corpus comprises over 780 songs composed by Trinh Cong Son and Bob Dylan. The research was conducted by means of questionnaires and interviews. The results showed how the two authors made use of metaphorical expressions of “Homeland” in their songs and hence, some similarities and differences between the two languages were explored as well. The author uses some methods in this study. However, the qualitative and quantitative are regarded as the two main approaches for the survey. It is expected that the findings will find out Cognitive Metaphors denoting the concept of “Homeland” in Trinh Cong Son’s versus Bob Dylan’s songs. Also, the researcher hopes interpret the similarities and differences of songs composed by Trinh Cong Son and Bob Dylan in terms of Cognitive Metaphors.
Master thesis in social sciences and humanitices
Keywords: investigation into cognitive metaphors of “homeland” in trinh cong son’s versus bob dyland’s songs; cognitive metaphors -- homeland